United States of America. Significant achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in the United States of America during 2019 are identified, with respect to the needs and interests of the country, strengthening technical relations with government agencies, relations with the Pan American Development Foundation (FUPAD), through of projects to include the role of rural women in agricultural processes. Likewise, it collaborated in the organization of the World Food Awards contest. Finally, work was done on fundraising and the development of agricultural studies.